1970
DOI: 10.13057/biodiv/d130404
|View full text |Cite
|
Sign up to set email alerts
|

Plants and animals diversity in Buqaty Mountain Area (BMA) in Hamadan Province, Iran

Abstract: Reyahi-Khoram M, Jafary M, Bayati M, Reyahi-Khoram R. 2012. Plants and animals diversity in Buqaty Mountain Area (BMA) in Hamadan Province, Iran. Biodiversitas 14: 190-194. Buqaty Mountain Area (BMA) is regarded as one of the genetic reserves of Hamadan province in Iran. BMA is highly important regarding variety of plant and animal species, but limited research work has been performed in this area in the field of biodiversity. Identifying the unique ecologic talents and capabilities and aesthetics of BMA is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Data obtained from other regions of Iran like Hormozgan [36], Kohgiluyeh and Boyer-Ahmad [28], Esfahan (Mobarakeh) [37], and Hamedan city [1, 34,35,38] showed that, Asteraceae, Lamiaceae and Apiaceae because of their wide range of biologically active compounds [39] were the most used families of medicinal plants for people's everyday health care needs. The use's frequency of the different plant parts in herbal remedy preparation is shown in Table 2 and Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained from other regions of Iran like Hormozgan [36], Kohgiluyeh and Boyer-Ahmad [28], Esfahan (Mobarakeh) [37], and Hamedan city [1, 34,35,38] showed that, Asteraceae, Lamiaceae and Apiaceae because of their wide range of biologically active compounds [39] were the most used families of medicinal plants for people's everyday health care needs. The use's frequency of the different plant parts in herbal remedy preparation is shown in Table 2 and Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…This study's data and observations obtained from village people were compared with information formerly recorded from other regions of Iran [28][29][30][31][32][33] as well as earlier data from the neighbor area in Hamedan city [3,34,35]. This is likely one of the first reports of some plant species being used in folk medicine in Qorveh-e Darjazin district of Hamedan, and unique research in Iran.…”
Section: Ethnomedicinal Plants Modes Of Preparation and Utilization Patternmentioning
confidence: 91%
“…Plant samples were identified and authenticated by Ramazan Kalvandi (scientific member of the Institute of Research and Education on Agriculture and Natural Resources in Hamedan, Iran) using standard procedures (Mozaffarian, 2006;Reyahi-khoram et al, 2012). The collected samples were cleaned using an air blower and dried in shadow (ambient temperature) for one week.…”
Section: Collection Of Plant Samplesmentioning
confidence: 99%